Super Capacitor Electronic Circuit Design for Wireless Charging - A. Hameed; Lway Faisal Abdulrazak; Zaid A. Aljawary (Institute of Advanced Engineering and Science, 2018)
Keeping time as base, a gadget has been proposed, where electrical accessories like Mobiles are charged within a fraction of minutes which is highly efficient and time saver as compared to the present time chargers which take nearly two hours to get fully charged. Objective of this project is to create a circuit which will be charged quickly and wireless. Wireless charging circuit works on the principle of inductive coupling. AC energy has been converted to DC energy through diode rectifier. Oscillator circuit produces high frequency passed by transmitter circuit to transmit magnetic field which is received by receiver circuit. A wireless charging concept with super capacitor will lead to faster charging and long operative life. Here super capacitor is used as a storage device. A Super capacitor has magnificent property, it can charge as well as discharge very quickly and linearly alike battery. The main difference between battery and super capacitor is specific energy, Super capacitor have 10-50 time less than battery.